Exploring Students’ Interpretation Skills on Data of Covid-19 Infographic Relating to Statistic - Sihotang, Rebecca Ester Marsaulina; Zulkardi, Zulkardi; Aisyah, Nyimas (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
This study aimed to determine the ability to interpret the Covid-19 infographic data relating to statistics. This research was a descriptive study with a qualitative approach and using online system. The data collection techniques are carried out through test of the ability of interpreting the Covid-19 infographic data and interview. The subjects of this study were students of grade VII, Junior High School 1 Palembang which consisted of 4 students with various ability. The most common indicators are reading simple graph, reading a trend in graph and extracting qualitative information from quantitative information. The least likely indicator is reading key features from graphs and comparing information from two graphs.